Strong Early Impact of Letrozole on Ovulation Induction Outperforms Clomiphene Citrate in Polycystic Ovary Syndrome - Rita Zsuzsanna Vajna; András Mihály Géczi; Fanni Adél Meznerics; Nándor Ács; Péter Hegyi; Emma Zoé Feig; Péter Fehérvári; Szilvia Kiss-Dala; Szabolcs Várbíró; Judit Réka Hetthessy; Levente Sára (MDPI AG, 2024)
Polycystic ovary syndrome is a common endocrine disorder, characterized by hyperandrogenism and/or chronic oligo/anovulation, which leads to infertility. The aim of this systematic review and meta-analysis was to explore the efficacy of letrozole compared with clomiphene citrate for ovulation induction in women with polycystic ovarian syndrome. The study protocol has been registered with PROSPERO (registration number CRD42022376611). The literature search included randomized clinical trials. We conducted our systematic literature search across three medical databases: MEDLINE (via PubMed), Cochrane Library (CENTRAL), and Embase. The data synthesis employed a random effects model. Out of the 1994 articles screened, 25 studies fulfilled the inclusion criteria. The letrozole group exhibited a significant increase in endometrial thickness (mean difference = 1.70, confidence interval: 0.55-2.86; I2 = 97%, p-value = 0.008). The odds of ovulation (odds ratio = 1.8, confidence interval: 1.21-2.69; I2 = 51%, p-value = 0.010) and pregnancy (odds ratio = 1.96, confidence interval: 1.37-2.81; I2 = 32%, p-value = 0.002) were significantly higher. The resistance index of the subendometrial arteries showed a significant decrease (mean difference = −0.15, confidence interval: −0.27 to −0.04; I2 = 92%, p-value = 0.030). Women diagnosed with polycystic ovarian syndrome and treated with letrozole for ovulation induction had increased ovulation and pregnancy rates and increased endometrial thickness. The lower resistance index of subendometrial arteries can enhance intrauterine circulation, creating more favorable conditions for embryo implantation and development.